The use of Read, Cover, Remember, Retell Strategy (RCRR) to Improve the Ninth Year Students’ Reading Comprehension of SMP Negeri 2 Parepare - Rubiah Rubiah; Amaluddin Amaluddin; Ammang Latifa (Universitas Muhammadiyah Enrekang, 2022)
The objective of the research was to find out whether there was any significant difference between the students who were taught through Read, Cover, Remember, Retell strategy (RCRR) and the students who were taught through Conventional Way (Collaborative Learning). This research used Quasi-Experimental Method. The population of this research was the nineth year students of SMP Negeri 2 Parepare. Total number of population was 256 students and two classes of them were taken as sample by using cluster random sampling. One class was as experimental group (IX.5) and one class was as control group (IX.7). The numbers of each class were 32 students. The instruments used were reading comprehension test. The result of this research concludes that there was any significant difference between the students between the students who were taught reading through RCRR strategy and the students who were taught reading through Conventional Way (Collaborative Learning). It is proved by the mean score of the students’ posttest in Experimental group was 85.46, while in Control group, the mean score of students’ posttest was 80.15. The result of the t-test value (3.123) was greater than t-table value (2.000). This indicated that H0 was rejected, and Hawas accepted.